(untitled) (Research, Society and Development, 2021)
Objective: present the feelings and perspectives of health professionals regarding the detection of the new coronavirus Methodology: descriptive-exploratory study of a qualitative nature, developed with 73 professionals from a hospital in the northwest of Paraná. The data were collected through semi-structured interviews, processed in the Interface of R pour les Analyzes Multidimensionally de Texts et de Questionnaires (IRAMUTEQ) using the word cloud resource. Results: the analysis of the interviews allowed the construction of three thematic categories: Motivation to perform the rapid test for Coronavirus; Protocols used to perform the rapid test in the professionals and Feelings experienced by the employees regarding the possibility of confirming a positive case in the team. Conclusion: given the perception of the professionals involved in this research, it can be confirmed that coping with Covid-19 represents a stressor showing that the concern and fear in the context of the pandemic, were often associated with the feelings of the participants in acquiring the virus and transmitting it to your family or people you love.